ON CARTESIAN PRODUCT OF CYCLES AND PATHS - Jumani, A. D. (The Nucleus, 2011)
Let G,H denote the Cartesian product of the graphs G and H and let γ(G,H) denote the domination number of the Cartesian product of the two simple graphs G and . In this note, the domination number of the Cartesian product , and is determined; that is H C3 n ,P C4,Pn C5,Pn 3 n γ(C ,P ) = n , 4 n γ(C ,P ) = n where n ≥ 1 and 5 n 5n 1 (C P ) 3 ⎢ ⎥ − γ = ⎢ ⎥ ⎣ ⎦ , where n 4 ≥ .